Identifying structural determinants of product specificity in Leishmania major farnesyl diphosphate synthase - Maheshwari, Sweta (Biochemistry, 2020)
Farnesyl diphosphate synthase (FPPS) is an isoprenoid chain elongation enzyme that catalyzes the sequential condensation of dimethylallyl diphosphate (DMAPP; C(5)) with isopentenyl diphosphate (IPP; C(5)) and the resulting geranyl diphosphate (GPP; C(10)) with another molecule of IPP, eventually producing farnesyl diphosphate (FPP; C(15)), which is a precursor for the biosynthesis of a vast majority of isoprenoids. Previous studies on FPPS have highlighted the importance of the structure around the hydrophobic chain elongation path in determining the product specificity. To investigate what structural features define the final chain length of the product in FPPS from Leishmania major, we designed and expressed six mutants of LmFPPS by replacing small amino acids around the binding pocket with bulky residues. Using enzymatic assays, binding kinetics and crystallographic studies, we analyzed the effects of these mutations on the activity and product specificity of FPPS. Our results revealed that replacement of Thr-164 with tryptophan and phenylalanine completely abolished the activity of FPPS. Intriguingly, T164Y substitution displayed dual product specificity and produced a mixture GPP and FPP as final products, with lower activity for FPP synthesis than that of the wild-type enzyme. These data indicate that Thr-164 is a potential regulator of product specificity.